The Relevance of English Teaching Materials for Primary Schools with Religious Moderation Values: A Review - M. Ali Ghufron; Taufiqur Rohman; M. Rifki Aditia (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
This research aimed to evaluate the relevance of the English teaching materials in the textbook “My Next Words (For Elementary School 5)” concerning the values of religious moderation as adopted in primary schools. The textbook has received endorsement from the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, highlighting the importance of evaluating its alignment with the government's religious moderation standards. The research methodology employed content analysis of the textbook to identify content related to religious moderation values. Surveys and interviews with elementary school teachers using this textbook provided insights into its utilization and its reflection of religious moderation values in teaching practices. The results indicated that the textbook primarily focuses on language skills, with limited integration of religious moderation values. It lacks sensitive language usage and activities promoting interfaith understanding. However, it does feature diverse character names associated with specific religious groups and incorporates some aspects of cultural diversity. Educators expressed the importance of integrating religious moderation values into English language teaching materials, but they found the current materials lacking in this regard. In conclusion, the textbook “My Next Words: For Elementary School” for Grade V requires improvements to better integrate religious moderation values. These enhancements will contribute to a more inclusive and relevant English language learning experience for elementary school students, fostering tolerance and interfaith harmony.